Analysis of capital structure stability of listed firms in China. Issue 2 (27th August 2019) - Kyissima, Kelvin Henry; Xue, Gong Zhang; Yapatake Kossele, Thales Pacific; Abeid, Ahmed Ramadhan
Abstract : Purpose: The purpose of this paper is to analyze the corporate capital structure stability of listed firms in China during the period 1990–2013. Design/methodology/approach: The study uses panel data from a sample of 716 firms that have been listed in China for at least 15 years. A fixed-effects panel data regression model with time effects is used in the estimation. Findings: The findings show that size, profitability and investment opportunities have a significant influence on capital structure, whereas the tangibility of assets is not found to be significant. Few industries show significance in explaining differences and variation in leverage ratios. Social implications: It is recommended by this study that corporate managers of listed firms in China should consider leverage ratios variation while choosing the capital structure. Originality/value: This study can be helpful in assisting companies to make financing decisions and setting up strategies relevant in their growth and profitability. The study will also have a significant assistance to bring to light corporate issues to policy makers, especially in the areas of both equity and debt financing, particularly the bond market. To the society, this study will show the nature of Chinese-listed companies, and it can assist individual investors in making decisions regarding companies in which they hold investments and in making meaningful comparisons with other companies. The paper also aims at contributing to the existing literature on the empirical study on capital structure.